Diagnostic efficiency of inflammatory signatures to distinguish isolated candidemia from candidemia with bacterial co-infection - Mnichowska-Polanowska, Magdalena; Grygorcewicz, Bartłomiej; Dołęgowska, Barbara; Boroń, Agnieszka; Michnowska, Agata; Jarosz, Konrad; Adamowicz, Magdalena; Wojciuk, Bartosz (Frontiers in Immunology, 2025)
IntroductionTo identify the differences in inflammatory response between critically ill patients responding to combined bacterial-fungal sepsis and those with isolated fungal sepsis.MethodsA retrospective case-control study compared ICU patients who were exposed (n=24) and unexposed (n=20) to candidemia. Two exposure modes were analyzed: isolated candidemia (C; n=12) versus candidemia with bacterial co-infection (BC; n=12). Targeted proximity extension assay (PEA) was used to examine differences in serum inflammatory proteome between groups. Differential inflammatory proteins served as input for a logistic regression model to validate their effectiveness in discrimination.ResultsTwo major clusters—candidemia cases and controls—were identified based on differential protein expression analysis. In five-fold cross-validation, LAP-TGF beta-1 was identified as the main driver, effectively distinguishing isolated candidemia [AUC 0.95; 95% CI 0.853–1.000]. TRANCE and IL-17C showed potential as a diagnostic signature indicating bacterial co-infection in the context of candidemia.DiscussionThe three-protein logistic regression panel (LAP-TGF beta-1, TRANCE and IL-17C) differentiated cases with isolated candidemia from those with candidemia and bacterial co-infection [AUC 0.82; 95% CI 0.629–0.968]. A three-protein inflammatory signature distinguished isolated fungal sepsis from combined bacterial-fungal sepsis. This study is the first to explore the inflammatory response to differentiate isolated candidemia from candidemia with bacterial co-infection.